Supereu: avesso do desejo - Ambertín, Marta Gerez (Percurso, 2009)
Realização: Andréa Carvalho Mendes de Almeida, Bela M. Sister, Danielle Breyton, Deborah Cardoso, Silvio Hotimsky e Susan Markuszower. Tradução: Stella Maris Schebli